2010
DOI: 10.2138/am.2010.3384
|View full text |Cite
|
Sign up to set email alerts
|

The incommensurately modulated structures of natural natrite at 120 and 293 K from synchrotron X-ray data

Abstract: The incommensurately modulated structure of the mineral natrite has been refined for the first time. Two single-crystal grains, Lv and Kh, from two different occurrences [Mt. Karnasurt, Lovozero massif (Lv), Kola peninsula, Russia, and the pegmatite of Mt. Koashva, Khibiny massif (Kh)], have been investigated at 293 and 120 K using synchrotron X-ray data. The average structures of both minerals are identical and the basic features of the structural modulations are similar to the synthetic γ-Na 2 CO 3 phase pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…The structural features of natrite have been thoroughly investigated in the recent past [4][5][6]. The more relevant feature of this compound is that at room temperature (RT) it is an incommensurately modulated phase characterized by very strong satellite reflections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural features of natrite have been thoroughly investigated in the recent past [4][5][6]. The more relevant feature of this compound is that at room temperature (RT) it is an incommensurately modulated phase characterized by very strong satellite reflections.…”
Section: Introductionmentioning
confidence: 99%
“…Such reflections result from a displacive modulation, in other words, from a stationary lattice wave in which each atom of the unit cell has its proper wave form, amplitude and phase, but all having the same modulation vector q ¼ q 1 a*þq 3 c* [7]. At RT, q 1 and q 2 take the values of ca 0.18 and 0.32, respectively [4,[6][7][8]. A continuous dependence of q on T has been reported in the 296-603 K thermal range [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This group seemed to be a completely rigid unit in the average structure of natrite refined by Zubkova et al (2002). Arakcheeva et al (2010), however, showed that the CÀO distances and the CÀO2ÀO1ÀO1 torsion angle (describing the deviation from planarity of the CO 3 entity) are slightly modulated along t, the additional coordinate in superspace. The reasons for such a modulation were described in detail by Arakcheeva and Chapuis (2005) for synthetic Na 2 CO 3 .…”
Section: Naturally Occurring Aperiodic Structuresmentioning
confidence: 98%
“…Karnasurt) and the Khibiny alkaline massif (Mt. Koashva), was studied in detail by Arakcheeva et al (2010) using the superspace approach. The average structure of natrite can be mainly described as graphite-like layers formed by Na3 and CO 3 ions, stacked along the c axis (Fig.…”
Section: Naturally Occurring Aperiodic Structuresmentioning
confidence: 99%
See 1 more Smart Citation